Legal Effectiveness of Neglect of the Elderly in Batam City: Challenges and Solutions - ratama, Jovan P; Nurlaily, Nurlaily; Tan, Winsherly (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2024)
Elderly neglect is a serious problem in Batam City triggered by rapid economic growth and changes in social life patterns. This research highlights the phenomenon of neglect of the elderly by families in the context of rapid economic growth and changing patterns of social life in Batam City. This research aims to explore and analyse how effective the law in Batam City is in protecting the elderly from family neglect; what is the phenomenon of neglect of the elderly by families in Batam City in the context of rapid economic growth and changing patterns of social life; and what solutions can be proposed to improve legal protection for marginalised elderly in Batam City. The research method used is qualitative research method, in this case the data obtained through face to face interviews with Orphanages and Hospitals in Batam City which will be reviewed through literature research and analysed juridically qualitatively. This research examines Law No. 13 of 1998 on the Welfare of the Elderly, Law No. 39 of 1999 on Human Rights, Law No. 23 of 2004 on the Elimination of Domestic Violence, Government Regulation No. 43 of 2004 on the Implementation of Efforts to Improve the Welfare of the Elderly and Regional Regulation of Batam City No. 4 of 2017 on the Implementation of Regional Health. The results show that the change from multigenerational families to nuclear families has reduced attention and care for the elderly, and law enforcement constraints, such as limited resources and the complexity of neglect cases, are serious challenges that need to be overcome.